From college composition to ESL: Negotiating professional identities, new understandings, and conflicting pedagogies. (August 2018) - Steadman, Angel; Kayi-Aydar, Hayriye; Vogel, Stefan M.
Abstract: This study examined how teaching assignments in the university's first-year composition program and graduate coursework informed six MA TESOL students' identity development and negotiations as ESL/EFL teachers in the United States. The collection and analysis of the data, which consisted of two sets of interviews and online discussion posts, were guided by poststructural understandings of identity. The findings describe the complex negotiations of participants' teacher identities, their new understandings about English and teaching, and the conflicting pedagogies they experienced. The article concludes by discussing the implications of this study for practitioners and teacher educators in TESOL, college composition, and teacher education programs.